2012
DOI: 10.1002/pon.3224
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress and its association with early retirement and subjective need for occupational rehabilitation in cancer patients

Abstract: Because occupational stress is associated with a higher risk of early retirement, both patients and physicians should take work-related problems seriously. Screening patients for occupational stress may help physicians identify patients who are at risk of experiencing problematic work re-entries. Furthermore, the results of the study suggest that cancer patients might have problems maintaining confidence in their abilities to solve work-related problems. Therefore, facilitating the development of a perception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 59 publications
1
8
0
3
Order By: Relevance
“…Second, interviews with BCNs indicate that patients showing signs of anxiety and distress were excluded from the trial. Mental health difficulties have been associated with employment-related outcomes; an observational study of 477 patients with cancer found that 19% were occupationally stressed, which increased their risk of early retirement (odds ratio 5.44) [68]. A relatively healthy participant group may partially explain why only two patients (28.6%) were referred to other services for support.…”
Section: Discussionmentioning
confidence: 99%
“…Second, interviews with BCNs indicate that patients showing signs of anxiety and distress were excluded from the trial. Mental health difficulties have been associated with employment-related outcomes; an observational study of 477 patients with cancer found that 19% were occupationally stressed, which increased their risk of early retirement (odds ratio 5.44) [68]. A relatively healthy participant group may partially explain why only two patients (28.6%) were referred to other services for support.…”
Section: Discussionmentioning
confidence: 99%
“…The occupational stress that working patients with cancer experience could end up causing further problems, including the need for formal rehabilitation down the line 10. One study of the coping strategies used by women with breast cancer highlighted the worth of actively reducing the workload, requesting flexible work arrangements and finding ways of making work tasks more manageable 17.…”
Section: Discussionmentioning
confidence: 99%
“…Patient education can empower them with knowledge about the impact of their condition, but we must note that whereas policies about giving patients information are standardised, for example,1–3 there is inevitable variation in the quality of patients’ experiences in cancer care,4–7 the lack of patient education could have an impact on symptoms. For example, many patients with cancer experience fatigue and lower cognitive or physical functioning,8 and difficulties in the ability to continue working,9 and 26% express a desire for rehabilitation 10. However, many find it difficult to find this support 11.…”
Section: Introductionmentioning
confidence: 99%
“…Both women (RR = 1.60, 95% CI 1.55–1.65) and men (RR = 1.55, 95% CI 1.46–1.65) who had been diagnosed with cancer were found to have an increased risk of early retirement compared to healthy controls (Carlsen, Oksbjerg Dalton, Frederiksen, Diderichsen, & Johansen, ). The observed risk factors for early retirement pension included older age, dissimilated disease, manual labour, sickness leave, physical and psychological comorbidity, low education and low income (Carlsen et al., ) as well as work‐related stressors (Böttcher, Steimann, Rotsch et al., ).…”
Section: Introductionmentioning
confidence: 99%